EFFECTIVE METHODS OF TAKING INTO ACCOUNT THE PSYCHOLOGICAL CHARACTERISTICS OF ADOLESCENTS IN THE EDUCATIONAL PROCESS - Venera Khamdamova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
A sharp change in the attitude to learning in adolescence, mental development in adolescence, arbitrary memory prevails, but involuntary memorization is also a teenage experience, the cognitive processes of adolescent students of secondary vocational educational institutions are qualitatively different from the cognitive processes of schoolchildren. In adolescents, the ability to switch and distribute attention is significant, its development and improvement are discussed in the article.